Development of a Dual-Stage CIM® CDI Reactor with Immobilized Glucuronan Lyases and Laccases for Sustainable Synthesis of Antioxidant Phenolized Oligoglucuronan - Xiaoyang Hou; Pascal Dubessay; Gwendoline Christophe; Nicolas Bridiau; Pierre-Edouard Bodet; Mounir Traikia; Mugilan Damadoran Raja; Thierry Maugard; Aleš Štrancar; Fabrice Audonnet; Philippe Michaud; Guillaume Pierre (Polysaccharides)
Immobilized enzyme reactors (IMERs) are critical tools for developing novel oligosaccharides based on the enzymatic catalysis of polysaccharides. In this paper, a novel glucuronan lyase from Peteryoungia rosettiformans was produced, purified, and then immobilized on a CIM® CDI disk for cleaving glucuronan. The results showed that around 63.6% of glycuronan lyases (800.9 μg) were immobilized on the disk. The Vmax values of immobilized glucuronan lyases did not significantly change (56.9 ± 4.7 μM∙min−1), while the Km values (0.310 ± 0.075 g∙L−1) increased by 2.5 times. It is worth noting that immobilized glucuronan lyases overcame the catalytic inhibition of free enzymes observed under high glucuronan concentrations (0.5–2 g∙L−1). circumscribed central composite design (CCCD) and response surface methodology (RSM) showed that glucuronan concentration, flow rate, and reaction time significantly affected the yield of oligoglucuronans. The degree of polymerization (DP) of degraded glucuronan ranged from DP 2–8 according to the results obtained by high performance anion exchange chromatography coupled with a pulsed amperometric detector (HPAEC-PAD). The IMER retained 50.9% activity after running 2373 column volumes of glucuronan. Finally, this glucuronan lyase reactor was tentatively connected to an immobilized laccase reactor to depolymerize, and gallic acid (GA) was added to glucuronan. Approximately 8.5 mg of GA was added onto 1 g of initial glucuronan, and the GA–oligoglucuronan conjugates showed notable antioxidant activity.